2022
DOI: 10.21203/rs.3.rs-1486539/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ultrahigh Dynamic Range and Low Noise Figure Programmable Integrated Microwave Photonic Filter

Abstract: Microwave photonics (MWP) has adopted a number of important concepts and technologies over the recent pasts, including photonic integration, versatile programmability, and techniques for enhancing key radio frequency performance metrics such as the noise figure and the dynamic range. However, to date, these aspects have not been achieved simultaneously in a single circuit. Here, we demonstrate, for the first time, a multi-functional integrated microwave photonic circuit that enables on-chip programmable filter… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Recent demonstrations of MWP filters with optimised link performance have come close to the target metrics, using a combination of fibre-based and chip-based components [45], [46], [158]. For example, Daulay et al reported an MWP filter using on-chip processing that achieved a link gain of 10 dB, and noise figure of 15 dB, and SFDR of 116 dB.Hz 2/3 [158]. This performance was enabled using low-biasing, high power lasers and optical amplifiers [158].…”
Section: B Integrated Platforms and Rf Link Performancementioning
confidence: 92%
See 4 more Smart Citations
“…Recent demonstrations of MWP filters with optimised link performance have come close to the target metrics, using a combination of fibre-based and chip-based components [45], [46], [158]. For example, Daulay et al reported an MWP filter using on-chip processing that achieved a link gain of 10 dB, and noise figure of 15 dB, and SFDR of 116 dB.Hz 2/3 [158]. This performance was enabled using low-biasing, high power lasers and optical amplifiers [158].…”
Section: B Integrated Platforms and Rf Link Performancementioning
confidence: 92%
“…However, most integrated microwave photonic systems do not meet these metrics, or do not report them. Recent demonstrations of MWP filters with optimised link performance have come close to the target metrics, using a combination of fibre-based and chip-based components [45], [46], [158]. For example, Daulay et al reported an MWP filter using on-chip processing that achieved a link gain of 10 dB, and noise figure of 15 dB, and SFDR of 116 dB.Hz 2/3 [158].…”
Section: B Integrated Platforms and Rf Link Performancementioning
confidence: 94%
See 3 more Smart Citations